Validitas dan Praktikalitas E-Modul Berbasis Inkuiri Terbimbing Terintegrasi Laboratorium Virtual pada Materi Hidrolisis Garam kelas XI SMA/MA - Fadhillah Fadhillah; Andromeda Andromeda (JURNAL EKSAKTA PENDIDIKAN (JEP), 2020)
E-modules are one of the innovations in the development of teaching materials that can be integrated with virtual laboratories. The learning model that can be applied in the development of e-modules is a guided inquiry learning model . This research aims to produce a salt hydrolisis e-module oriented on guided inquiry learning model integrated with virtual laboratories and reveal the validity and practicality of e-modules. The type of this research is research and development (R&D). the method used in this research is developmental model by using 4-D or 4-P design. They are define, design, develop and disseminate. This research is limited to the stage of development, the validity and practicality test. The data collection instrument is a questionnaire of validity and practicality. The e-module was validated by 6 experts, they are 3 chemistry lectures of FMIPA UNP and 3 chemistry teachers while practicality test was carried out by 2 chemistry teachers and 15 XII grade students of MIPA SMAS Adabiah 2 Padang. data from validity and practicality test results were analyzed using the cohen kappa formula. Based on the results of the study, it was found that average kappa moment of validity test was 0,83 with a very high validity category, the average kappa moment of teacher practicality was 0,82 with a very high practicality category and the average kappa moment students practicality was 0,82 with a very high practicality category. The results of the analysis of students answer on e-module, it was found average of key question was 90%, average of worksheet was 94,8% and average of evaluation test was 90%. Thus, it was concluded that the salt hydrolysis e-module based on guided inquiry learning virtual laboratories integrated was produced was valid and practical.